Edgar Rubin and Psychology in Denmark Figure and Ground - Pind, Jörgen L. (History and Philosophy of Psychology,, 2014)
Is it a glass centerpiece--or is it really two faces? The familiar optical illusion known as the Rubin Vase embodies the complexities of the brain's recognition of visual figures and backgrounds. Its creator's accomplishments, however, extend far beyond this well-known concept. Edgar Rubin and Psychology in Denmark tours a tumultuous century of history, politics, culture, and thought as reflected in the intellectual life of Denmark following the Golden Age of Kierkegaard and H. C. Andersen. Rubin's scholarly journey takes him from the debate over the scientific study of "the soul" to the maturation of perceptual psychology, providing both human context for our modern understanding of consciousness and a timeline for the recognition of psychology as science. Besides his revolutionary discoveries in visual perception, less-known aspects of his work are explored, such as his observations on taste and the perception of speech, as is his relationship--and reluctant contribution--to Gestalt theory. In these pages, Rubin is portrayed as a thinker simultaneously of his time and place and distinctly universal and modern. Included in this fascinating biography:  The role of philosophy in the development of psychology. From psychophysics to experimental psychology. The education of psychologists. Rubin and the phenomenological approach in psychology. The impact of Rubin’s work on Visually Experienced Figures and why it still resonates today. Setback and perseverance during World War Two. Niels Bohr and Edgar Rubin. Rubin's later work and legacy to modern psychology. For those interested in the history of psychology and the history of ideas, and for students and specialists in perceptual psychology, Edgar Rubin and Psychology in Denmark will inform, inspire, and even delight.